Ultrasonic Testing of Diffusion Bonded Joints of AlMg3 - Nachtnebl, Pavel; Kolarik, Ladislav; Forejtova, Lucie; Reisgen, Uwe; Behr, Wilfried (Manufacturing Technology Journal, 2018)
The Diffusion welding was used to join aluminium alloy AlMg3 in order to make ultrasonic testing of diffusion bonded joints and analyse diffusion process. This ultrasonic testing should be used to compare with other non-destructive testing methods which the Institute of Manufacturing Technology of CTU in Prague develop. The paper discusses the ultrasonic testing for the diffusion bonded joints of AlMg3 and magnesium oxide which was created and which had an influence on quality of the diffusion bonded joints. The Alloy AlMg3 was selected because of easy correlation with welding parameters, ultrasonic testing, metallographic examination and preparation of samples for the diffusion welding.
Keywords: diffusion welding; AlMg3; magnesium oxide; ultrasonic testing